Docosanoids Promote Neurogenesis and Angiogenesis, Blood-Brain Barrier Integrity, Penumbra Protection, and Neurobehavioral Recovery After Experimental Ischemic Stroke - Belayev, Ludmila (2018)
Docosahexaenoic acid (DHA) and neuroprotectin D1 (NPD1) are neuroprotective after experimental ischemic stroke. To explore underlying mechanisms, SD rats underwent 2 h of middle cerebral artery occlusion (MCAo) and treated with DHA (5 mg/kg, IV) or NPD1 (5 μg/per rat, ICV) and vehicles 1 h after. Neuro-behavioral assessments was conducted on days 1, 2, and 3, and on week 1, 2, 3, or 4. BrdU was injected on days 4, 5, and 6, immunohistochemistry was performed on week 2 or 4, MRI on day 7, and lipidomic analysis at 4 and 5 h after onset of stroke. DHA improved short- and long-term behavioral functions and reduced cortical, subcortical, and total infarct volumes (by 42, 47, and 31%, respectively) after 2 weeks and reduced tissue loss by 50% after 4 weeks. DHA increased the number of BrdU+/Ki-67+, BrdU+/DCX+, and BrdU+/NeuN+ cells in the cortex, subventricular zone, and dentate gyrus and potentiated NPD1 synthesis in the penumbra at 5 h after MCAo. NPD1 improved behavior, reduced lesion volumes, protected ischemic penumbra, increased NeuN, GFAP, SMI-71-positive cells and vessels, axonal regeneration in the penumbra, and attenuated blood-brain barrier (BBB) after MCAo. We conclude that docosanoid administration increases neurogenesis and angiogenesis, activates NPD1 synthesis in the penumbra, and diminishes BBB permeability, which correlates to long-term neurobehavioral recovery after experimental ischemic stroke.